Epigenetic targeting of MECOM/KRAS axis by JIB-04 impairs tumorigenesis and cisplatin resistance in MECOM-amplified ovarian cancer - Ibha Singh; Amarnath Karna; Anita Prajapati; Ujjawal Solanki; Archana Mukherjee; Sheetal Uppal; Pawan Malhotra; Manoj Kumar; Pallavi Agarwal (Cell Death Discovery)
Abstract Copy number gene amplification and associated overexpression of driver oncogenes are genetic events that contribute to cancer progression and drug resistance. MDS1 and EVI1 Complex locus (MECOM) gene is copy number amplified and overexpressed in aggressive epithelial ovarian cancers. The biological function and precise molecular mechanism of MECOM in the progression and drug resistance of ovarian cancer remain unclear. Here, we unravel MECOM as a regulator of KRAS and its downstream MAP Kinase signalling pathway, and also identify epigenetic inhibitor JIB-04 as a pharmacological agent targeting MECOM/KRAS axis. RNAi-mediated attenuation of MECOM in ovarian cancer cells harboring MECOM amplification reduced their proliferation, impaired colony formation, and impeded cellular migration. ChIP-qPCR analysis confirmed binding of MECOM to the KRAS promoter, suggesting direct regulation of the KRAS gene at the transcriptional level. Further, MECOM promoted cellular proliferation by regulating KRAS-mediated ERK/ZEB1 signalling cascade. The anti-tumorigenic effects due to MECOM loss were phenocopied by the treatment of ovarian cancer cells harboring MECOM amplification with JIB-04 epigenetic inhibitor targeting Jumonji domain histone demethylase enzymes. By ChIP-qPCR, we show that JIB-04 induced transcriptional changes of MECOM by altering H3K27me3 demethylation at its promoter region. We further report that ovarian cancer cells expressing high-MECOM levels exhibit cisplatin resistance, which could be effectively reversed upon pre-treatment with JIB-04. The therapeutic efficacy of JIB-04 was further demonstrated in mice bearing ovarian cancer cell xenografts, where JIB-04 slowed down the tumor growth in corroboration with diminishing MECOM expression. RNA-sequencing analysis identified potential cisplatin resistance gene, SUB1, being regulated by JIB-04-mediated modulation of MECOM expression. Altogether, these data suggest that epigenetic silencing of MECOM by JIB-04 mediated H3K27me3 modulation is an important mechanism in ovarian cancer and provide a new therapeutic target for the treatment of ovarian cancers harboring MECOM amplification.